Entrepreneur self-efficacy and performance outcome of small-scale business operators at the border towns of Malaysia and Thailand - Mansor, Mohd Najib; Othman, Abdul Rahim; Abdul Manaf, Kamarul Bahrain; Don, Mohd Sobri (INSInet Publications, 2014)
Background : Small-scale individual entrepreneurs (SIEs) play an important role for the national economy. Realizing this, the Malaysian government has put many efforts to help these SIEs to develop their business. To achieve the objective of having many successful businesses, it is important to understand the attribute of the entrepreneurs that would drive them to become successful. Objective: This paper examines the relationship between entrepreneur self-efficacy and performance outcome of small scale business operators at the border towns of Malaysia and Thailand.The research is a cross-sectional study and a survey method is used. Results: Data from 355 Small- Scale Individual Entrepreneurs (SIEs) were analyzed and the result shows a positive and significant relationship between entrepreneur self-efficacy and performance outcome. Conclusion:Our result is consistent with those studies conducted in western countries.It seems that the small scale business operators at border town of Malaysia and Thailand have the same belief which is not different from those in western countries.